2014
DOI: 10.1371/journal.pmed.1001753
|View full text |Cite
|
Sign up to set email alerts
|

Association of Adenotonsillectomy with Asthma Outcomes in Children: A Longitudinal Database Analysis

Abstract: Rakesh Bhattacharjee and colleagues use data from a US private health insurance database to compare asthma severity measures in children one year before and one year after they underwent adenotonsillectomy with asthma measures in those who did not undergo adenotonsillectomy. Please see later in the article for the Editors' Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 53 publications
2
55
0
2
Order By: Relevance
“…While individual response to ETA or ITA is likely mul- 31 Several studies [32][33][34][35] have confirmed that patients with asthma are more likely to develop symptoms of OSAS. A recent study 36 also found that after adenotonsillectomy, children with asthma had a significant reduction in asthma exacerbation, hospitalization, and emergency department visits. Based on our results, it would be relevant to identify if there was any variance in resolution of asthma symptoms according to the specific type of surgical technique for adenotonsillectomy that was performed.…”
Section: Overnight Psgmentioning
confidence: 89%
“…While individual response to ETA or ITA is likely mul- 31 Several studies [32][33][34][35] have confirmed that patients with asthma are more likely to develop symptoms of OSAS. A recent study 36 also found that after adenotonsillectomy, children with asthma had a significant reduction in asthma exacerbation, hospitalization, and emergency department visits. Based on our results, it would be relevant to identify if there was any variance in resolution of asthma symptoms according to the specific type of surgical technique for adenotonsillectomy that was performed.…”
Section: Overnight Psgmentioning
confidence: 89%
“…In a class III report, SDB was a predictor of asthma severity, and in two retrospective cohort studies, adenotonsillectomy was accompanied by improved asthma outcomes (class II and IV) [116][117][118].…”
Section: Literature Review A)mentioning
confidence: 96%
“…18 Furthermore, improvements in nocturnal asthma symptoms and asthma-specific quality of life also have been reported in adults with asthma treated with continuous positive airway pressure therapy for coexistent OSA. 19 Even though the foregoing studies were observational in nature, the findings suggest that the treatment of OSA may help improve asthma control in some children.…”
Section: Impact Of Sdb Treatments On Asthma Controlmentioning
confidence: 94%